Styl mediálního dialogu a vyjednávání pozic (na příkladu jedné české talk show) - Hoffmannová, Jana (Stylistyka, 2010)
The paper discusses the style o f conversation in a Czech talk show called “Všechnopárty”, and the negotiation of positions in this type of media dialogue. It compares different distribution o f positions in three talk shows of Czech television and tries to define some more or less fixed features of this genre (such as asymmetry, or the dominant function of entertainment). A special attention is given to the role of the variety of Czech that is used by the hosts and guests in positioning: it seems that the talk show is a type of a private conversation w ith the participants using particularly colloquial Czech. Nevertheless, different sociolects of the interlocutors (who belong to different generations and professional groups) are an important component of the positioning and permanent negotiation.